Enhancing Repurchase Intention: The Impact of Service Quality and Facilities at Garuda Pontianak Hotel - Juliandi; Sukardi (Jurnal Manajemen Bisnis, 2024)
This research aims to find out whether there is a relationship between service quality and facilities. With a positive data collection strategy and a sample size of 100 participants, this research applies associative methodology. Participants must be customers who have used Garuda Pontianak hotel services at least twice, in order to be considered for taking part in this research. Statistical methods used in the analysis include: multiple linear regression, correlation and determination coefficients, simultaneous testing (F test), and partial testing (t test). The data are linear, normally distributed, and show no signs of multicollinearity; these findings were confirmed by standard assumption tests. The variables included in this study contributed 61% of the variance in repurchase interest, while the remaining 39% was influenced by other factors that could not be explained. Initial research shows that the quality of services and facilities available at the Garuda Pontianak hotel has a significant effect on repurchase interest for users of Garuda hotel services in Pontianak City.